2020
DOI: 10.1007/s12182-020-00515-0
|View full text |Cite
|
Sign up to set email alerts
|

Insights into kinetic inhibition effects of MEG, PVP, and L-tyrosine aqueous solutions on natural gas hydrate formation

Abstract: It is necessary to understand all the prerequisites, which result in gas hydrate formation for safe design and control of a variety of processes in petroleum industry. Thermodynamic hydrate inhibitors (THIs) are normally used to preclude gas hydrate formation by shifting hydrate stability region to lower temperatures and higher pressures. Sometimes, it is difficult to avoid hydrate formation and hydrates will form anyway. In this situation, kinetic hydrate inhibitors (KHIs) can be used to postpone formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The comparison made in terms of inhibition strength (°C) when compared in terms of systems with brine water gave a higher inhibition strength for all inhibitors, which is around 0.4 °C; however, in terms of inhibitors, mSA-RmAFP1 gave the highest inhibition strength of around 5.5 °C. After that come PVP at 4 °C and then glycine at 3 °C, and Saberi 90 studied the impact of PVP on the induction time with two different concentrations, 1 and 2 wt % of l -tyrosine, 1 wt % of MEG, and 10 wt % and a mix of MEG and PVP on different concentrations and 2 wt % of PVP + 10 wt % of MEG and 2 wt % of PVP + 20 wt % of MEG using Stainless Steel (SS-316) on CH 4 hydrate with mineral oil with 40% water cut under 8 MPa pressure and 4.7 °C temperature. It has been reported that PVP gave the highest induction time around 85 min compared to MEG at 51 min, but after mixing PVP and MEG the induction time was increased.…”
Section: Application Of Khis In Oil-based Systemsmentioning
confidence: 99%
“…The comparison made in terms of inhibition strength (°C) when compared in terms of systems with brine water gave a higher inhibition strength for all inhibitors, which is around 0.4 °C; however, in terms of inhibitors, mSA-RmAFP1 gave the highest inhibition strength of around 5.5 °C. After that come PVP at 4 °C and then glycine at 3 °C, and Saberi 90 studied the impact of PVP on the induction time with two different concentrations, 1 and 2 wt % of l -tyrosine, 1 wt % of MEG, and 10 wt % and a mix of MEG and PVP on different concentrations and 2 wt % of PVP + 10 wt % of MEG and 2 wt % of PVP + 20 wt % of MEG using Stainless Steel (SS-316) on CH 4 hydrate with mineral oil with 40% water cut under 8 MPa pressure and 4.7 °C temperature. It has been reported that PVP gave the highest induction time around 85 min compared to MEG at 51 min, but after mixing PVP and MEG the induction time was increased.…”
Section: Application Of Khis In Oil-based Systemsmentioning
confidence: 99%
“…However, because of the excess amount requirements (35–50% of the water flow rate) and the toxic elements associated with THIs, researchers are working on low-dosage kinetic hydrate inhibitors (KHIs) that could be economical and environmentally responsible, as only 0.5% of the water flow rate or less is required to inhibit hydrates . Note that low-dosage KHIs slow down the hydrate formation process but do not change the thermodynamic state of the system, as opposed to the THIs …”
Section: Introductionmentioning
confidence: 99%
“…39 Note that low-dosage KHIs slow down the hydrate formation process but do not change the thermodynamic state of the system, as opposed to the THIs. 40 For a deepwater pipeline in the Gulf of Mexico, KHIs were considered for hydrate prevention. For cost savings, two scenarios were considered: (1) using a THI (e.g., methanol) and (2) using a KHI alone.…”
Section: Introductionmentioning
confidence: 99%
“…Gas hydrate, a type of cage-like crystal structure constructed by water and gas molecules, is generally formed in a low-temperature and high-pressure environment. The gas molecules, such as methane, ethane, carbon dioxide, and so forth, are able to be enveloped by the cages of water molecules, forming structure I, II, and H hydrate. The formation of hydrate becomes a challenge in the development of deep-water fields, where the oil or gas is exposed to the environment of high pressure, low temperature, and water cuts. , Therefore, hydrate forms more easily in the deep water environment and increases the risk of plugging pipelines. Webb et al studied the effect of water fraction in a water-in-dodecane emulsion on the rheological behavior of a hydrate slurry via a high-pressure rheology apparatus. The results show that the viscosity of the hydrate slurry increases apparently with the increase of water fraction from 5 to 30%.…”
Section: Introductionmentioning
confidence: 99%